European and Eurasian Union: The Clash of Integrations - Sytin, Alexander (Skhid, 2015)
In the article author compares two alternative integration projects, in whichRussiawas involved with a different degree of intensity during the post-Soviet period. Based on the material of a significant number of sources, author shows the main milestones of the project of European integration ofRussiauntil its collapse because of the conflict betweenRussiaand Western partners. The project of Eurasian integration is also analyzed in the paper, and its hopelessness because of the failure of the Kremlin's policy towardsUkraineand other partners. It is demonstrated in the article, that project of Eurasian integration and creating of Eurasian Union is the attempt ofRussian Federationto build the international association withRussiain the role of main and active partner and Kremlin as a political center. This politics ofRussiais one of the main reasons of closing the project of Eurasian integration.